Exploring safety systems for dispensing in community pharmacies: focusing on how staff relate to organizational components - Harvey, Jasmine; Avery, Anthony J.; Ashcroft, Darren; Boyd, Matthew; Phipps, Denham L.; Barber, Nicholas (Elsevier, 2015)
Background: Identifying risk is an important facet of a safety practice in an organization. To identify risk, all components within a system of operation should be considered. In clinical safety practice, a team of people, technologies, procedures and protocols, management structure and environment have been identified as key components in a system of operation. Objectives: To explore risks in relation to prescription dispensing in community pharmacies by taking into account relationships between key components that relate to the dispensing process. Methods: Fifteen community pharmacies in England with varied characteristics were identified, and data were collected using non-participant observations, shadowing and interviews. Approximately 360 hours of observations and 38 interviews were conducted by the team. Observation field notes from each pharmacy were written into case studies. Overall, 52,500 words from 15 case studies and interview transcripts were analyzed using thematic and line-by-line analyses. Validation techniques included multiple data collectors co-authoring each case study for consensus, review of case studies by members of the wider team including academic and practicing community pharmacists, and patient safety experts and two presentations (internally and externally) to review and discuss findings. Results: Risks identified were related to relationships between people and other key components in dispensing. This included how different levels of staff communicated internally and externally, followed procedures, interacted with technical systems, worked with management, and engaged with the environment. In a dispensing journey, the following categories were identified which show how risks are inextricably linked through relationships between human components and other key components: 1) dispensing with divided attention; 2) dispensing under pressure; 3) dispensing in a restricted space or environment; and, 4) managing external influences. Conclusions: To identify and evaluate risks effectively, an approach that includes understanding relationships between key components in dispensing is required. Since teams of people in community pharmacies are a key dispensing component, and therefore part of the operational process, it is important to note how they relate to other components in the environment within which they operate. Pharmacies can take the opportunity to reflect on the organization of their systems and review in particular how they can improve on the four key categories identified.